Leadership strategies for the hybrid workforce : how to manage complexity and maintain effectiveness using the CAARE framework to support hybrid workers - Hill, N. Sharon (MIT Sloan Management Review, 2023)
Leaders of hybrid teams — where employees alternate between working in the office and working remotely — face the challenge of providing flexibility while maintaining group effectiveness and cohesion. The author describes the CAARE framework, a new approach to leading hybrid work that combines the elements of configuration, autonomy-alignment, relationships, and equity to help leaders balance individual flexibility with group effectiveness.